Sesbania phosphorus requirements when used as biofertilizer for long-term rice cultivation - Ventura, W.; Ladha, J.K. (Wiley, 1997)
Green manures may affect the long‐term nutrient supplying capacity of soils. In a long‐term trial that compared the performance of azolla (Azolla microphylla Lam.), sesbania (Sesbania rostrata Bremek. and Oberm.), urea, and no fertilizer N on rice (Oryza sativa L.), a progressive decline in the growth of and N accumulation by sesbania was observed after the ninth crop. This study examined the reasons for sesbania decline with emphasis on the effect of fertilizer P on sesbania performance in relation to soil available P, cropping history, and moisture regime. In the 1992 dry season (14th crop), sesbania performance with and without P was determined in (i) field microplots within main long‐term plots, and (ii) pots containing soil monoliths from long‐term plots. Without P fertilizer, sesbania grew poorly and accumulated <40 kg N ha−1. But addition of 28.4 kg P ha−1 increased sesbania N accumulation 3 to 11 fold and the greater N availability increased rice production. Addition of P improved sesbania biomass and N accumulation in dried‐flooded and continuously flooded regimes but not in the dried‐moist regime. Sesbania P requirements were greater than for rice. Continuous rice‐sesbania cropping without addition of P limited sesbania growth, N accumulation, and green manure value even though it did not limit rice production, suggesting that the P requirements will be greater for a long‐term rice cropping system that depends solely on green manure N than for rice grown with fertilizer N.